2019
DOI: 10.3390/pr8010029
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Potentially Toxic Elements Pollution from Mineral Processing Steps at Xikuangshan Antimony Plant, Hunan, China

Abstract: We evaluated the direct release to the environment of a number of potentially toxic elements (PTEs) from various processing nodes at Xikuangshan Antimony Mine in Hunan Province, China. Sampling wastewater, processing dust, and solid waste and characterizing PTE content (major elements Sb, As, Zn, and associated Hg, Pb, and Cd) from processing activities, we extrapolated findings to assess wider environmental significance using the pollution index and the potential ecological risk index. The Sb, As, and Zn in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The P i of Sb had a maximum value of each site. Sb pollution was the most serious element in soil, consistent with the finding of the wastewater, dust, and tailings produced from discharge points at the antimony mineral processing plant of XKS [14]. For all the metals at SXN and SXS, P i > 1, and it was also found SXN had the highest P Sb (902.57 ± 910.98, average ± standard deviation, hereafter the same), indicating an extensive Cr/Zn/Cd/Pb/As/Hg/Sb multi-pollution at SXN and SXS.…”
Section: Pollution Index Evaluation Of Ptessupporting
confidence: 82%
See 2 more Smart Citations
“…The P i of Sb had a maximum value of each site. Sb pollution was the most serious element in soil, consistent with the finding of the wastewater, dust, and tailings produced from discharge points at the antimony mineral processing plant of XKS [14]. For all the metals at SXN and SXS, P i > 1, and it was also found SXN had the highest P Sb (902.57 ± 910.98, average ± standard deviation, hereafter the same), indicating an extensive Cr/Zn/Cd/Pb/As/Hg/Sb multi-pollution at SXN and SXS.…”
Section: Pollution Index Evaluation Of Ptessupporting
confidence: 82%
“…As the metal with the most potential risk, Sb posed the highest ecological risk in SXN, SZS, and SXS, reaching 6317.99, 5784.30, and 3979.18, respectively, followed by SYA (1403.32). The E Sb of soils surrounding the tailings reservoir in the north of XKS reached 10548.42, indicating very high ecological risk [14]. Based on the average RI values (Figure 4) of all seven PTEs, the analysis showed that, overall, sites were at very high ecological risk.…”
Section: Evaluation Of Potential Ecological Risks Of Ptesmentioning
confidence: 95%
See 1 more Smart Citation
“…The existing studies on the changes of the rhizosphere environment mostly focus on the changes of heavy metal content in rhizosphere soil solution and the changes of plants' effective state of heavy metals. More studies on the morphological changes of heavy metals in soil solid phase use rhizosphere bags, rhizosphere boxes, and other artificial rhizosphere environments [9,10]. This simulated rhizosphere environment is different from the growth environment of natural plants.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [22] evaluated the direct release to the environment of a number of potentially toxic elements (PTEs) from various processing nodes at Xikuangshan Antimony Mine in Hunan Province, China. Sampling wastewater, processing dust, and solid waste and characterising PTE content (major elements Sb, As, Zn, and associated Hg, Pb, and Cd) from processing activities, we extrapolated findings to assess wider environmental significance using the pollution index and the potential ecological risk index.…”
mentioning
confidence: 99%